An Egyptian Revolution Novel From Naguıb Mahfouz: Karnak Cafe - Bülent KORKMAZ (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2017)
In this article, first a brief biography of Naguib Mahfouz, then a short summary of his novel entitled Karnak Cafe are given. Following the examination of the historical background of the novel, a fictional analysis of the novel’s structure is presented.